(untitled) (Vietnam Journal of Community Medicine, 2026)
Malocclusion is a prevalent condition in dentistry, negatively impacting both oral health and psychological well-being. Objective: This study aimed to assess the prevalence of malocclusion using the Medit i700 intraoral scanner and to evaluate the orthodontic treatment needs among dental students at Hai Phong University of Medicine and Pharmacy in 2025. Methods: A cross-sectional descriptive study was conducted on 75 students (38 males, 50.7%; 37 females, 49.3%) selected through total sampling. Results: The overall prevalence of malocclusion was 86.70%. Class III malocclusion was the most common (40%), followed by Class I (29.3%) and Class II (17.3%). The oval arch form was predominant, observed in 66.7% of upper arches and 65.3% of lower arches. According to the Index of Orthodontic Treatment Need (IOTN), 85.3% of students required orthodontic treatment based on dental health and aesthetic components. Conclusion: The findings indicate a high prevalence of malocclusion. Notably, the need for treatment due to dental health reasons (84%) was significantly higher than for aesthetic reasons (68%), highlighting that functional and structural occlusal issues should be the primary concern in this population.